Severe Hyperbilirubinemia: A Rare Complication of Lyme Disease - Maarij Baig; Lin Zheng; Alka Farmer (Case Reports in Gastrointestinal Medicine)
Gastrointestinal signs and symptoms are common in the early stages of Lyme disease. However, hyperbilirubinemia from Lyme disease is extremely uncommon. There are only two case reports in literature attributing Lyme disease to hyperbilirubinemia. Here we report a case of severe hyperbilirubinemia as the presenting symptom of Lyme disease. Other plausible etiologies have been ruled out after extensive workups, including liver biopsy. His hyperbilirubinemia gradually resolved after being started on doxycycline. With high incidence of Lyme disease, it should be considered for patients who present with hyperbilirubinemia in endemic areas with possible tick exposure.